2017
DOI: 10.3126/jssn.v18i1.17207
|View full text |Cite
|
Sign up to set email alerts
|

Torg’s ratio in normal adult nepalese population

Abstract: Introduction: Acute cervical trauma occasionally leads to cervical canal stenosis in some individuals in spite of minor trauma. The spinal canal-to-vertebral body ratio (Torg-Pavlov ratio) has been proposed for assessing developmental spinal canal stenosis. It is not affected by magnification, and is measured on lateral plain films of cervical vertebrae. The result of this study may help in better understanding of the Torg's ratio, which is more reliable than direct measuring of the mid-sagittal diameter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The values of the present study was comparable to that of the work done by Rijal B et al (0.99±0.09 to 1.01±0.07mm) and larger to that reported by Singh et al (0.97±0.13mm). 10,12 In the cervical spine, the span of TR in the Koreans (0.90±0.11 to 1.05±0.10mm) and Indians (0.95±0.06 to 1.08±0.07mm) was similar. 16,20 Including ours, the values of these studies indicated stenosis free cervical canal.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The values of the present study was comparable to that of the work done by Rijal B et al (0.99±0.09 to 1.01±0.07mm) and larger to that reported by Singh et al (0.97±0.13mm). 10,12 In the cervical spine, the span of TR in the Koreans (0.90±0.11 to 1.05±0.10mm) and Indians (0.95±0.06 to 1.08±0.07mm) was similar. 16,20 Including ours, the values of these studies indicated stenosis free cervical canal.…”
Section: Discussionmentioning
confidence: 94%
“…4,15,16 In the study by Nepal P. et al on Nepalese population the VBW was smaller (14.57±1.24 to 15.41±1.75mm) than the present study with larger values (17.81±1.73mm) reported by Singh et al on the same population than ours. [10][11][12] The morphometry of cervical pedicle is used in transpedicular screw fixation and to determine the size of the screw to be used during surgical treatment. Our measurements of PH and PW revealed a tendency which was comparable to the Chinese (5.7± 0.4 to 7.2± 0.7 mm and 4.4± 1.0 to 5.8± 0.6 mm, respectively) and Brazilian (6.8±0.86 to 7.3±0.83 and 5.1±0.78 to 6.8±0.97 mm, respectively) study but larger than the Indian (6.15±0.9 to 6.75±1.09 and 4.89±0.88 to 6.19±1.01mm, respectively) report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…canal-body ratio is taken as an index for calculating the degree of stenosis. 2 The measurement of dimensions of the lumbar canal and body has thus become an important tool for the diagnosis and treatment of spinal stenosis. 3 - 5 …”
Section: Introductionmentioning
confidence: 99%